Reviewing Trust Issues in Cloud Computing. Issue 1 (July 2021) - Singh, Amanpreet; Kaur, Amandeep; Gupta, Deepali
Abstract: Cloud computing is a technique to minimize the use of hardware and software infrastructure digitally for the dynamic delivery of services. There are numerous components of current cloud computing models: end-user computers, networks of contacts, access management systems, and infrastructures of applications. Different organizations of cloud computing are providing various policies for handling tasks of cloud vendors and consumers. During task migration, whenever data is transferred over the cloud from one node to another; then the sink node should be trustworthy. It becomes a challenging task to create reliable and trustworthy cloud platforms. As the base from the concept of cloud computing, many authors proposed data privacy, security problems, security challenges, trust models, trust issues, challenges of trust management In this paper, we highlight some of the trust issues faced by both cloud vendors and cloud customers while using cloud services.